Relationship Between Historical Lameness, Medication Usage, Surgery, and Exercise With Catastrophic Musculoskeletal Injury in Racehorses - Hitchens, Peta L.; Hill, Ashley E.; Stover, Susan M. (Frontiers in Veterinary Science, 2018)
Background: The rate of catastrophic musculoskeletal injuries (CMI) in racehorses is high in the United States compared to other countries. Few modifiable risk factors related to lameness, medication, and surgery history have been identified. Objective: To detect management factors that increase risk of CMI by comparing medical histories between horses that sustained, and horses that did not sustain, a CMI. Study design: Case-control. Methods: Racehorse necropsy data (May 2012-June 2013) were obtained through the California Horse Racing Board Postmortem Program. Attending veterinarians of Thoroughbreds (TB) and Quarter Horses (QH) that experienced CMI, and of three matched control horses, were invited to complete an online veterinary medical history survey. We investigated associations between CMI and lameness, medication, surgery, and exercise history using multivariable logistic regression. Results: There were 146 TB (45 cases, 101 controls) and 17 QH (11 cases, 6 controls) surveys completed. TB cases were more likely to show signs of lameness within the three months prior to death compared to controls. A high proportion of both cases (64.3%) and controls (76.8%) were administered medications, but unraced TB case horses were more likely to have been administered systemic medications compared to those that previously raced. TB cases were more likely to have raced with greater intensity during their career, but had eased off in the month preceding CMI. For QHs, there was insufficient power to detect significant differences between cases and controls that showed signs of lameness, or that were administered medications. Surgery history was not associated with CMI. Main limitation: Insufficient power to detect small effect sizes. Conclusions: The study provides information that can be used to aid in identification of horses at high risk for catastrophic injury, and management factors that can be modified to reduce the risk for all horses.